2016
DOI: 10.4103/2229-5151.195448
|View full text |Cite
|
Sign up to set email alerts
|

Early high ratio platelet transfusion in trauma resuscitation and its outcomes

Abstract: Introduction:The optimal ratio of platelets (PLTs) to packed red blood cell (PRBC) in trauma patients requiring massive transfusion protocol (MTP) is still controversial. This report aims to describe the effect of attaining a high PLT:PRBC ratio (≥1:1.5) within 4 h postinjury on the outcomes of trauma patients receiving MTP.Methods:Over a 24-month period, records of all adult patients with traumatic injury who received MTP were retrospectively reviewed. Data were analyzed with respect to PLT:PRBC ratio ([high-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…Consumption coagulopathy and platelet dysfunction are prominent features of severe hemorrhagic shock. [20] In the present study, we found lower mean platelet counts and increased INR in abdominal trauma patients with mortality when compared to patients without mortality. This is a reflection of the degree of blood loss that resulted in platelet dysfunction and coagulopathy due to consumption.…”
Section: Discussionsupporting
confidence: 56%
“…Consumption coagulopathy and platelet dysfunction are prominent features of severe hemorrhagic shock. [20] In the present study, we found lower mean platelet counts and increased INR in abdominal trauma patients with mortality when compared to patients without mortality. This is a reflection of the degree of blood loss that resulted in platelet dysfunction and coagulopathy due to consumption.…”
Section: Discussionsupporting
confidence: 56%
“…Significant protective association between higher platelet ratios and mortality was concentrated during the first 6 h only, in contrast to high plasma ratios, which were protective throughout the first 24 h [576]. A recent observational study confirms that a high platelet:RBC ratio (≥ 1:1.5) within 4 h post-injury but not later (4–24 h) is significantly associated with a lower rate of multiple organ failure and mortality within 30 days post-injury, although with higher rates of wound infection and pneumonia [686].…”
Section: Resultsmentioning
confidence: 99%
“…Evidence also suggests that platelet aggregation, and more so platelet contributions to clot stiffness, can become impaired almost immediately after severe trauma, suggesting that intrinsic platelet dysfunction also plays an important role in the development of TIC 42 44 . Platelet function, when measured at Emergency Department arrival, is also strongly associated with mortality and blood transfusion requirements 42 , 45 , and high ratios of platelet to packed red blood cell transfusions during trauma resuscitation are associated with decreased mortality 46 . Clinical measurement of platelet function has been typically measured by platelet count, which, when decreased, is related to mortality after trauma 47 .…”
Section: Resultsmentioning
confidence: 99%